Public transport service quality: Policy prioritization strategy in the importance-performance analysis and the three-factor theory frameworks. (December 2022) - Tuan, Vu Anh; Van Truong, Nguyen; Tetsuo, Shimizu; An, Nguyen Ngoc
Highlights: A rigorous analytical framework was utilized to identify an appropriate service quality analysis method. The three-factor theory was superior to the IPA due to the non-linear and asymmetric relations between service quality factors and rider satisfaction. All the service factors were found to be performance factors for captive riders. Eight of nine factors were performance for non-captive (vehicle-owned) riders, while environment friendliness was excitement. This is the first study using the three-factor theory in Vietnam. Abstract: Service quality is a determinant of increasing public transport rider satisfaction. However, understanding of service quality and satisfaction relations has been limited. This study seeks an appropriate method to demonstrate the nature of service quality-satisfaction relations. Thereby, research results can be methodologically, theoretically, and empirically defensible. The importance-performance analysis (IPA) and the three-factor theory, the most widely preferred for public transport service quality prioritization based on the importance of service factors to rider satisfaction, will be utilized. The study takes transit service in Ho Chi Minh City (HCMC), Vietnam, to demonstrate that the three-factor theory, which has been limitedly utilized despite being more advantageous and robust, is superior to the IPA. Although the extent to which the service quality factors affect satisfaction varied across rider segments, the types of service quality factors were found consistent. For example, captive riders considered all service factors as performance. Non-captive riders considered the environment factor as excitement. No basic factor was found across rider groups. This study contributes to the limited understanding of the non-linear and asymmetric relations between service quality and satisfaction of various rider groups, which is rarely found in transit service quality literature. Furthermore, it introduced a case study of Vietnamese urban transit services for the first time. It suggests that enhancing passenger information, rider care, and comfort are recommended as the most practical and economical measures in the short run. However, the city government should improve availability and accessibility to promote public transport ridership in the long run.